Iconic expression in the designs of bullying posters - Lina Saad Hashim; Maha Moayed Abdel Hussein Nasser (الاكاديمي)
The poster is one of the important media in the communication process, as it effectively contributes to spreading the necessary awareness and building a community culture that views health phenomena in society as topics that must be coexisted with naturally. In turn, we participate in addressing this phenomenon and reducing it by designing posters for student age groups. To deal with this phenomenon in a humane way that differs from bullying, so the researcher raised the following question to express the problem of her research: What is the iconic expression in the designs of posters for the phenomenon of bullying?